Sosialisasi Pencegahan Bullying Bagi Siswa Sekolah di SMP Negeri 80 Jakarta - Dirgantini, Marissa Kemala; Purbowati, Lindri; Cendhayanie, Rara Amalia; Pramudita, Tito; Dzulkarnain, Ariefin; Khaerani, Fatih; Silalahi, Ronaldo Saputra; Atmoko, Dwi; Hunny, Aura Tria; Juniati, Puput Aulia; Nuriyah, Sitta; Sugeng (Abdi Bhara, 2025)
Bullying behavior is a behavior that harms people or other parties. Bullying usually        occurs in schools. Victims of bullying usually experience academic decline and mental damage and hopes for the future. In the socialization activity of bullying prevention for school students carried out at SMP Negeri 80 Jakarta. The purpose of     this activity is so that students at the school are able to prevent and overcome the dangers of bullying in schools through the understanding provided by the speakers. As is known, along with the development of the era and different economic levels, it creates a gap for each person's status as a basis for carrying out bullying. Then there is the process of delivering material in this activity through lectures, discussions and questions and answers and conducting evaluations through Pre-Tests and Post-Tests.      With this activity, it is hoped that students will have sufficient knowledge about bullying and the legal regulations that govern it so that they are careful in their attitudes and are able to work together with their classmates. The continuity and peace of a school in principle requires cooperation between the school community and parents in providing understanding and coordinating each other to create intelligent and high-achieving students in the future.